Three-dimensional architecture and paleoenvironments of Osaka Bay : an integrated seismic study on the evolutionary processes of a tectonic basin /: an integrated seismic study on the evolutionary processes of a tectonic basin. ([2019]) - Itoh, Yasuto; Takemura, Keiji
No abstract available